“Institution Building” at CIVA: Experimenting with Institutional Critique Through Architectural Exhibition - Arianna Casarini (Museum, Materials and Discussions)
Despite the rising interest in the production of institutional histories, the field of institutional critique applied to the contemporary architectural institution is still an emerging framework of research and debate, both inside and outside this specific category of cultural institution. Due to the dominantly projective nature of the architectural institution, its critique tends to associate with and translate into proactive attempts at reimagining and rebuilding the institution. Institutional critique thus merges in the architectural context with the idea of the blueprint and the manifesto, and it is articulated in often collaborative and experimental formats. Through the exploration of the architectural exhibition “Institution Building” organized by the CIVA of Bruxelles in 2021, this article aims to analyze the use of the exhibition as a methodology for proposing a critique of the architectural institution, and to reflect on its effectiveness as a means to produce and mediate a critical discourse around the organization, functioning, and operations of the architectural institution.